Single-staged Treatment Using a Standardized Protocol Results in Functional Motion in the Majority of Patients With a Terrible Triad Elbow Injury - Gupta, Akash (Springer US, 2014)
BACKGROUND: Terrible triad injuries of the elbow, defined as elbow dislocation with associated fractures to the radial head and coronoid, are associated with stiffness, pain, and loss of motion. Studies to date have consisted of small sample sizes and used heterogeneous surgical techniques, which render comparisons difficult and unreliable. QUESTIONS/PURPOSES: In a group of patients treated under a standard surgical protocol, we sought to determine the early dislocation rate, the range of motion in those not undergoing secondary procedures, the frequency and types of secondary surgical interventions required, the difference in motion between those undergoing secondary surgery and those who did not, and the frequency of heterotopic ossification and patient-reported stiffness. METHODS: Patients underwent a surgical protocol that involved fixing the coronoid, fixing the radial head if possible, otherwise performing radial head arthroplasty, and repairing the lateral ligamentous structures. Patients were excluded if ipsilateral upper extremity fractures from the humerus to the distal forearm were present. Fifty-two patients had a minimum followup of 6 weeks and were included for the early dislocation rate, and 34 of these (65%) had a minimum of 6 months followup and were included for the rest of the data. Eighteen of the 52 (35%) were considered lost to followup because they were seen for less than 6 months postsurgically and were excluded from further analysis. Chart review was performed to determine the presence of early dislocation within the first 6 weeks after surgery, range of motion in patients not requiring a secondary procedure, the frequency and types of secondary procedures required, the range of motion before and after a secondary procedure if it was required, and postoperative stiffness. Postoperative radiographs were analyzed to determine the presence and severity of heterotopic ossification. RESULTS: One of 52 patients sustained a dislocation within the first weeks of surgery (1.9%). Those not undergoing a secondary procedure were able to achieve a flexion arc of 110° and a supination-pronation arc of 148°. Nine of 34 patients (26%) underwent a secondary surgical procedure with stiffness, heterotopic ossification, and ulnar neuropathy being the most common surgical indications. Before secondary surgical procedures, patients had a flexion arc of 57° and a supination-pronation arc of 55°, which was less than those only requiring primary surgery alone (p < 0.001). After secondary surgery, patients were able to achieve a flexion arc of 96° and a supination-pronation arc of 124°, which was not different from those who did not undergo reoperation (p = 0.09 and p = 0.08, respectively). Twenty-eight of 34 patients demonstrated evidence of heterotopic ossification on radiographs, whereas 20 patients, including all nine undergoing secondary procedures, reported stiffness at the elbow. CONCLUSIONS: Using a standardized surgical protocol, a low early dislocation rate was observed, although stiffness remains a challenge. Many patients who initially do not attain functional range of motion can usually attain this after secondary procedures aimed at removing the heterotopic ossification. LEVEL OF EVIDENCE: Level IV, therapeutic study. See guidelines for authors for a complete description of levels of evidence.